Ottoman Empire and channels in foreign policy of the Western powers in 1914-1918 - Chupekov, A. A.; Izbassarova, L. T. (Journal of Oriental Studies, 2016)
This article about English, French and German interests are examined in Ottomam Empire in 1914-1918. The internal position and diplomatic position of this state, his place in the international arena.